2010
DOI: 10.1007/s00432-010-0773-3
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of human MDA-MB-435S tumor by U6 promoter-driven short hairpin RNAs targeting focal adhesion kinase

Abstract: These results indicate that the systemic delivery of plasmid DNA targeting FAK function using cationic liposome as a gene carrier, represents a promising avenue for breast cancer therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…7 Various studies have indicated that down-regulation of focal adhesion kinase expression may represent a potential therapeutic approach, retarding the unlimited proliferation and apoptosis suppression seen in various neoplasms such as malignant glioma, colon carcinoma and breast cancer. [4][5][6] However, the effect of focal adhesion kinase on cellular apoptosis and proliferation within laryngeal squamous cell carcinoma still remains unclear. In the current study, we investigated whether focal adhesion kinase contributes to apoptosis inhibition and proliferation promotion in laryngeal cancer, by assessing focal adhesion kinase expression in laryngeal cancer cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Various studies have indicated that down-regulation of focal adhesion kinase expression may represent a potential therapeutic approach, retarding the unlimited proliferation and apoptosis suppression seen in various neoplasms such as malignant glioma, colon carcinoma and breast cancer. [4][5][6] However, the effect of focal adhesion kinase on cellular apoptosis and proliferation within laryngeal squamous cell carcinoma still remains unclear. In the current study, we investigated whether focal adhesion kinase contributes to apoptosis inhibition and proliferation promotion in laryngeal cancer, by assessing focal adhesion kinase expression in laryngeal cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…3 Previous studies have demonstrated that focal adhesion kinase is involved in regulating cellular proliferation in several different types of tumours. [4][5][6] Other authors have found that focal adhesion kinase influences cell apoptosis in a variety of tumours. 4,5,7,8 To the best of our knowledge, no previous studies have assessed the in vivo relationship between focal adhesion kinase expression and cellular proliferation and apoptosis within laryngeal squamous cell carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the gene delivery system we utilized was the same as previously reported (35,36), which proved to efficiently increase the therapeutic efficacy of the survivinT34A plasmid. Our previous biodistribution studies have showed that cationic lipid-DNA complexes was accumulated mainly in tumor tissues (37). This is due to the leaky microvasculature in tumors that could facilitate extravasation, and thus, increase the permeability of tumor vessels to liposomes.…”
Section: Discussionmentioning
confidence: 99%
“…FAK activity can be altered, and its expression can be usually up-regulated in tumors [6][7][8]. FAK inhibition could result in cell detached [9], apoptotic [10,11], decrease cell proliferation [12], migration [13] and invasion [10,14]. Moreover, the up-regulated FAK could enhance tumor metastasis and cause the poor prognosis for patients [14][15][16], and it was also reported may be closely associated with the development of the malignant phenotypes in colorectal carcinoma and hepatocellular carcinoma [14,17].…”
Section: Introductionmentioning
confidence: 99%